Squamous cell carcinoma of the scalp with intracranial extension – the importance of various imaging modalities - Stošić, Srdjan; Juković, Mirela; Golubović, Jagoš; Panjković, Milana; Stojanović, Sanja (Vojnosanitetski pregled, 2023)
Introduction. Around 2% of all cutaneous neoplasms arise in the scalp and can be classified as either primary or metastatic. The intracranial extension is rare in cutaneous malignancies but can generally occur if left untreated. Squamous cell carcinoma (SCC) is the second most common type of nonmelanoma skin cancer after basal cell carcinoma. About 3–8% of SCCs are located on the scalp and can cause skull and dural invasion in rare cases. Case report. A 49-year-old male patient presented with a large and painful lesion in the parietooccipital region of the head. Magnetic resonance imaging (MRI) revealed a large inhomogeneous, necrotic lesion with infiltration of the underlying skull and dura. The patient underwent surgical removal of the tumor with excision of invaded skin, bone, and dura with a safety margin of 1 cm, followed by custom prefabricated 3D-printed cranioplasty with polymethylmetacrilate. Pathohistological analysis revealed invasive SCC with immunohistochemistry staining revealing CK5/6 and CK7 positivity. Conclusion. Some cases of scalp SCCs can cause invasion of the underlying skull and dura if left untreated. Imaging modalities like computed tomography (CT) and MRI play a crucial role in evaluating the degree of neoplastic extension and potential calvarial and dural invasion, thus being of significant importance in preoperative planning and management.
Keywords: diagnosis; histological techniques; immunohistochemistry; magnetic resonance imaging; neoplasm invasiveness; neoplasms, squamous cell; neurosurgical procedures; scalp